Genetic Counselling and Testing for Hereditary Breast and Ovarian Cancer: The Gent(le) Approach. Issue 1 (17th June 2013) - De Vos, M.; Poppe, B.; Delvaux, I.; Mortier, G.; Claes, K.; Messiaen, L.; De Paepe, A.
Abstract : The counselling experience with 50 Flemish families in whom mutation analysis of the total coding region of the BRCA1 and BRCA2 gene has been initiated, is presented. Genetic testing for breast-ovarian cancer susceptibility is offered by a multidisciplinary team. During the counselling sessions, special attention is given to comprehensible and emotionally acceptable communi-cation of genetic information and to the psychosocial evaluation of the counselee. The limitations of molecular testing and the controversy surrounding cancer prevention strategies are also discussed. The overall acceptance of mutation testing is high. Some of the problems encountered are inaccuracy of the reported family history, poor retrieval of the medical records of affected family members and the reluctance of many patients to inform their relatives about the possibility of being tested.